2022
DOI: 10.1021/acs.jnatprod.1c00837
|View full text |Cite
|
Sign up to set email alerts
|

Nyuzenamide C, an Antiangiogenic Epoxy Cinnamic Acid-Containing Bicyclic Peptide from a Riverine Streptomyces sp.

Abstract: A new nonribosomal peptide, nyuzenamide C (1), was discovered from riverine sediment-derived Streptomyces sp. DM14. Comprehensive analysis of the spectroscopic data of nyuzenamide C (1) revealed that 1 has a bicyclic backbone composed of six common amino acid residues (Asn, Leu, Pro, Gly, Val, and Thr) and four nonproteinogenic amino acid units, including hydroxyglycine, β-hydroxyphenylalanine, p-hydroxyphenylglycine, and 3,β-dihydroxytyrosine, along with 1,2-epoxypropyl cinnamic acid. The absolute configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…Epoxinnamide ( 1 ) is structurally related to nyuzenamides A-C ( Figures S2 and S7 ), as they also have a bicyclic deca-depsipeptide backbone tethered with an alkenyl cinnamic acid-derived acyl chain [ 16 , 21 ]. However, they have two different amino acids in their deca-peptide cycles: 1 possesses β -hydroxyleucine and threonine instead of β -hydroxyphenylalanine and valine incorporated in the nyuzenamides.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Epoxinnamide ( 1 ) is structurally related to nyuzenamides A-C ( Figures S2 and S7 ), as they also have a bicyclic deca-depsipeptide backbone tethered with an alkenyl cinnamic acid-derived acyl chain [ 16 , 21 ]. However, they have two different amino acids in their deca-peptide cycles: 1 possesses β -hydroxyleucine and threonine instead of β -hydroxyphenylalanine and valine incorporated in the nyuzenamides.…”
Section: Resultsmentioning
confidence: 99%
“…N11-34 and DM14) revealed that these strains are phylogenetically distinct consistently with the structural difference of epoxinnamide and the nyuzenamides ( Figure S12 ). The epoxy cinnamic acid moiety is very unique and has been extremely rarely reported in nature, with only nyuzenamide C and NC-1 as examples [ 12 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations